Methods for Measuring Nitrogen Release from Controlled-Release Fertilizer Used for Vegetable Production - Monica Ozores-Hampton; Luther C. Carson (EDIS)
Enhanced-efficiency fertilizers are a group of fertilizers that reduce the risk of nutrient loss to the environment and subsequently increase fertilizer use efficiency. This increase may be accomplished through maintaining nutrients in the root zone by physical barriers, reduced solubility, or retaining nutrients in a less leachable form. This 7-page fact sheet examines laboratory, growth chamber, greenhouse, and field methods for measuring nitrogen release in controlled-release fertilizers. Written by Monica Ozores-Hampton and Luther C. Carson, and published by the UF Department of Horticultural Sciences, August 2013.